2020
DOI: 10.1111/pce.13740
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of putrescine accumulated under potassium deficiency?

Abstract: Biomarker metabolites are of increasing interest in crops since they open avenues for precision agriculture, whereby nutritional needs and stresses can be monitored optimally. Putrescine has the potential to be a useful biomarker to reveal potassium (K + ) deficiency. In fact, although this diamine has also been observed to increase during other stresses such as drought, cold or heavy metals, respective changes are comparably low. Due to its multifaceted biochemical properties, several roles for putrescine und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 172 publications
2
46
0
1
Order By: Relevance
“…This suggests that there was an increase in polyamines biosynthesis, which was perhaps associated with the urea cycle (urea was not significantly increased in roots under our conditions). Polyamines play a role in tolerance against abiotic stress, including hypoxia [ 39 , 40 , 41 ]. In addition, it has been proposed that the involvement of amino acid metabolism and polyamines under waterlogging could reflect an aspartate cycle [ 26 ], whereby arginine synthesis would represent a source of fumarate (citrulline + aspartate →→ arginine + fumarate), consumes reducing equivalents, and might be degraded to NO.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there was an increase in polyamines biosynthesis, which was perhaps associated with the urea cycle (urea was not significantly increased in roots under our conditions). Polyamines play a role in tolerance against abiotic stress, including hypoxia [ 39 , 40 , 41 ]. In addition, it has been proposed that the involvement of amino acid metabolism and polyamines under waterlogging could reflect an aspartate cycle [ 26 ], whereby arginine synthesis would represent a source of fumarate (citrulline + aspartate →→ arginine + fumarate), consumes reducing equivalents, and might be degraded to NO.…”
Section: Discussionmentioning
confidence: 99%
“…PAs are acknowledged regulators of plant stress responses, and Spd and Spm are generally considered to play more important roles than Put (Liu, Wang, Wu, Gong, & Moriguchi, 2015). Whereas, Put has specific functions that differ from those of Spd and Spm in countering abiotic stresses, such as potassium deficiency (Cui, Pottosin, Lamade, & Tcherkez, 2020). Overexpression of ADC , an arginine decarboxylase gene encoding a key enzyme involved in Put synthesis, can improve stress tolerance of plants, but it should be considered that toxic effects of Put over‐production have also been observed, and the deleterious effects may be caused by enhanced DAO activity and excessive ROS production (Cui et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, Put has specific functions that differ from those of Spd and Spm in countering abiotic stresses, such as potassium deficiency (Cui, Pottosin, Lamade, & Tcherkez, 2020). Overexpression of ADC , an arginine decarboxylase gene encoding a key enzyme involved in Put synthesis, can improve stress tolerance of plants, but it should be considered that toxic effects of Put over‐production have also been observed, and the deleterious effects may be caused by enhanced DAO activity and excessive ROS production (Cui et al, 2020). Here, we found that exogenous EBL can promote the accumulation of Spd and Spm, but decrease the level of Put, and the transformation of Put to Spd and Spm was beneficial to plant salt tolerance; however, when plants did not require large amounts of BR under low‐salt stress, excessive application of EBL promoted Put oxidation, and produced large amounts of H 2 O 2 , which harmed plants.…”
Section: Discussionmentioning
confidence: 99%
“…Com a evolução da carência em K, essas manchas aumentaram de tamanho, no sentido da nervura principal, coalescem e atingiram a maior parte da área foliar, cujo tecido, posteriormente, necrosou (Figura 8). Essa necrose é causada pelo acúmulo da putrescina (Mengel, 2007;Prado, 2008;Hawkesford et al, 2012), a qual em nível tóxico induz a oxidação enzimática de compostos fenólicos pelas enzimas peroxidase e polifenol oxidase, o que resulta no escurecimento de tecidos vegetais (Whitehead & Swardt, 1982;Cui et al, 2020). Sintomas semelhantes foram observados por Casas & Casas (1999) e Rincón (2005), mas diferentes aos encontrados por Almeida et al (2011).…”
Section: Potássiounclassified